2019
DOI: 10.1371/journal.pone.0219945
|View full text |Cite
|
Sign up to set email alerts
|

Selection and promotion processes are not associated by the relative age effect in an elite Spanish soccer academy

Abstract: The aim of this study was to analyze the influence of the relative age effect (RAE) on the selection and promotion processes in an elite soccer academy. One hundred and eleven elite youth players who belonged to an elite soccer club from the Spanish “La Liga” participated in this study. Players were classified into three age-categories: under 14 years (U14), under 16 years (U16) and under 18 years (U18); and they were also classified in quartiles based on their date of birth (i.e., January-March, Q1; April-Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
6
21
0
Order By: Relevance
“…Specifically, our results demonstrate that between U11 to U21 groups, retained players were typically superior in physical performance tests, where effect sizes were typically small to medium (Table 2). This corroborates with previous findings that retained players within European football academies 25,35,43 and Australian football 55 achieved superior physical performances. Buchheit et al reported that performances on field tests were related to match-running performance (in a positiondependent manner) 56 , where superior match-running performance is also related to retention across age groups within an English academy 57 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, our results demonstrate that between U11 to U21 groups, retained players were typically superior in physical performance tests, where effect sizes were typically small to medium (Table 2). This corroborates with previous findings that retained players within European football academies 25,35,43 and Australian football 55 achieved superior physical performances. Buchheit et al reported that performances on field tests were related to match-running performance (in a positiondependent manner) 56 , where superior match-running performance is also related to retention across age groups within an English academy 57 .…”
Section: Discussionsupporting
confidence: 93%
“…To the authors' awareness, the relationship between birth date and retention/dropout, after selection into an elite youth academy, has seldom been addressed within previous research 9,34 . Still, our results corroborate the findings within a Spanish football academy, in which birth date was not associated with being retained or promoted to a higher playing level between U14 and U18 groups 35 . However, it must be acknowledged that the low number of Q3 and Q4 players within the current study represent drawbacks in the analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An additional uncertainty factor is age, as reported in [51], where the race speed becomes minimal for athletes aged 25-29 years. The effect of age in different sports has been discussed [51,52], as well as the effects of race distance and gender [53]. In general, women differ from men in thermal responses because of a larger ratio of body surface to body mass, a greater subcutaneous fat content, and lower exercise capacity [1,53].…”
Section: Discussionmentioning
confidence: 99%
“…Age consider as a factor that determining RAE. More specifically previous studies have mentioned that RAE decreased as age increased (Brustio et al, 2018;Castillo et al, 2019). However, Mujika et al, (2009) performed a study on players' of Athletic Club Bilbao, and mentioned that the effect of RAE is independent of players' age.…”
mentioning
confidence: 93%